Governor's Talk Highlights Fine Farewell Program - Vallejo Times-Herald (Vallejo Times-Herald)
Vallejo will give a practical demonstration of its good wishes to the hungry children of Europe today when state and local civic leaders join with thousands of communityminded citizens to bid "God speed" to the Friend Ship Golden Bear. Tons of food and clothing destined for destitute families in Europe will leave today aboard the California Maritime Academy training ship after elaborate farewell ceremonies headed by Governor Earl Warren.